Human Escherichia coli isolates from hemocultures: Septicemia linked to urogenital tract infections is caused by isolates harboring more virulence genes than bacteraemia linked to other conditions - Micenková, Lenka; Beňová, Alžbeta; Frankovičová, Lucia; Bosák, Juraj; Vrba, Martin; Ševčíková, Alena; Kmeťová, Marta; Šmajs, David (International journal of medical microbiology, 2017)
Escherichia coli is the most common cause of bloodstream infections and community-acquired sepsis. The main aim of this study was to determine virulence characteristics of E. coli isolates from hemocultures of patients with a primary disease of urogenital tract, digestive system, a neoplastic blood disease, or other conditions. Results from a set of 314 E. coli isolates from hemocultures were compared to data from a previously published analysis of 1283 fecal commensal E. coli isolates. Genetic profiling of the 314 E. coli isolates involved determination of phylogenetic group (A, B1, B2, D, C, E, and F), identification of 21 virulence factors, as well as 30 bacteriocin-encoding determinants. Pulsed-field gel electrophoresis was used to analyze clonal character of the hemoculture-derived isolates. The E. coli isolates from hemocultures belonged mainly to phylogenetic groups B2 (59.9%) and D (21.0%), and less frequently to phylogroups A (10.2%) and B1 (5.7%). Commonly detected virulence factors included adhesins (fimA 92.0%, pap 47.1%, and sfa 26.8%), and iron-uptake encoding genes (fyuA 87.9%, fepC 79.6%, aer 70.7%, iucC 68.2%, and ireA 13.7%), followed by colibactin (pks island 31.5%), and cytotoxic necrotizing factor (cnf1 11.1%). A higher frequency of microcin producers (and microcin M determinant) and a lower frequency of colicin Ib and microcin B17 was found in hemoculture-derived isolates compared to commensal fecal isolates. E. coli isolates from hemocultures harbored more virulence genes compared to fecal E. coli isolates. In addition, hemoculture E. coli isolates from patients with primary diagnosis related to urogenital tract were clearly different and more virulence genes were detected in these isolates compared to both fecal isolates and hemoculture-derived isolates from patients with blood and gastrointestinal diseases.
Keywords: infekce vyvolané Escherichia coli; Escherichia coli Infections; Infant; Humans; infekce močového ústrojí; Phylogeny; kojenec; lidé středního věku; Sepsis; dítě; pulzní gelová elektroforéza; Child; koliciny; Female; Aged; mladý dospělý; dospělí; Virulence; sepse; Escherichia coli; Electrophoresis, Gel, Pulsed-Field; senioři; lidé; Genotype; Hemoculture; faktory virulence; Colicins; předškolní dítě; Adult; Phylogenetic group; ženské pohlaví; Male; Middle Aged; fylogeneze; Adolescent; Neoplasms; Aged, 80 and over; Gastroenteritis; Bacteriocin; nádory; Young Adult; Blood; E. coli; senioři nad 80 let; genotyp; Urinary Tract Infections; mužské pohlaví; Child, Preschool; gastroenteritida; Virulence Factors; mladiství